Antibiotic resistance indicator genes in biofilm and planktonic microbial communities after wastewater discharge - Haenelt, Sarah; Richnow, Hans-Hermann; Müller, Jochen A.; Musat, Niculina (Frontiers in Microbiology, 2023)
The spread of bacteria with antibiotic resistance genes (ARGs) in aquatic ecosystems is of growing concern as this can pose a risk of transmission to humans and animals. While the impact of wastewater treatment plant (WWTP) effluent on ARG abundance in surface waters has been studied extensively, less is known about the fate of ARGs in biofilms. The close proximity and dense growth of microorganisms in combination with the accumulation of higher antibiotic concentrations in biofilms might render biofilms a reservoir for ARGs. Seasonal parameters such as water temperature, precipitation, and antibiotic concentrations should be considered as well, as they may further influence the fate of ARGs in aquatic ecosystems.Here we investigated the effect of WWTP effluent on the abundance of the sulfonamide resistance genes sul1 and sul2, and the integrase gene intI1 in biofilm and surface water compartments of a river in Germany with a gradient of anthropogenic impact using quantitative PCR. Furthermore, we analyzed the bacterial community structure in both compartments via 16S rRNA gene amplicon sequencing, following the river downstream. Additionally, conventional water parameters and sulfonamide concentrations were measured, and seasonal aspects were considered by comparing the fate of ARGs and bacterial community diversity between summer and winter season.2 Our results show that biofilm compartments near the WWTP had a higher relative abundance of ARGs (up to 4.7 %) than surface waters (< 2.8 %). Sulfonamide resistance genes were more persistent further downstream (>10 km) the WWTP in the hot and dry summer season than in winter. This finding is likely a consequence of the higher proportion of wastewater and thus wastewater-derived microorganisms in the river during summer periods. We observed distinct bacterial communities and ARG abundance between the biofilm and surface water compartment, but even greater variations when considering seasonal and spatiotemporal parameters. This underscores the need to consider seasonal aspects when studying the fate of ARGs in aquatic ecosystems.